2020
DOI: 10.2147/opth.s238686
|View full text |Cite
|
Sign up to set email alerts
|

<p>How Can We Improve Toric Intraocular Lens Calculation Methods? Current Insights</p>

Abstract: In this paper, we review current strategies for calculating toric intraocular lenses (IOLs). We discuss the prevalence and clinical relevance of astigmatism and the assessment of toric IOL candidates. We detail recommendations for evaluating astigmatism and current biometry and IOL power calculation techniques. Finally, error sources and results of current toric IOL calculators are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…3 However, patients who have undergone prior refractive surgery and those who require toric IOL correction or incisional keratotomy may require additional calculations performed with special formulas, such as the Barrett True K or the Barrett Toric Formula, and these formulas do not uniformly reside on biometry machines, necessitating transfer of the data to a separate system for surgical planning. 4 This transfer of data introduces the possibility of transcription errors and consumes significant time. Considering that errors in transcribing numbers from one platform to another are possible, manual transcription of information critical to the refractive outcome is certainly not ideal.…”
Section: Video Abstractmentioning
confidence: 99%
“…3 However, patients who have undergone prior refractive surgery and those who require toric IOL correction or incisional keratotomy may require additional calculations performed with special formulas, such as the Barrett True K or the Barrett Toric Formula, and these formulas do not uniformly reside on biometry machines, necessitating transfer of the data to a separate system for surgical planning. 4 This transfer of data introduces the possibility of transcription errors and consumes significant time. Considering that errors in transcribing numbers from one platform to another are possible, manual transcription of information critical to the refractive outcome is certainly not ideal.…”
Section: Video Abstractmentioning
confidence: 99%
“…Previous studies showed that using traditional formulas will bring only 26–35% of eyes to within 0.5D of the targeted astigmatism in regular corneas 37 , with a post-operative residual astigmatism of − 0.64 ± 0.43D 15 , − 0.71 ± 0.43D 16 and − 1.03 ± 0.79D 38 . Other studies described that IOL power calculation is considerably less accurate in keratoconus than in typical eyes 17 , 18 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study group, mean change in corneal astigmatism was 0.28 D. This change is in line with the previous publications reporting corneal astigmatism change of 0.1 to 0.3 in a standard phacoemulsification cataract surgery with a 2.4 mm corneal incision. 30,31 In terms of visual acuity outcomes, previous studies investigating long-term outcomes in eyes with AC IOL report CDVA of 20/64 to 20/60 at final follow-up. 15,32,33 With the presented technique, CDVA results were noninferior (20/70-20/40) to those previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…In our study group, mean change in corneal astigmatism was 0.28 D. This change is in line with the previous publications reporting corneal astigmatism change of 0.1 to 0.3 in a standard phacoemulsification cataract surgery with a 2.4 mm corneal incision. 30,31…”
Section: Discussionmentioning
confidence: 99%